Respuesta :
Answer:
- C) 4x⁴ + 14x²y + 49y²
Step-by-step explanation:
Given expression
- 24x⁶ - 1029y³
Factorize it as follows:
- 24x⁶ - 1029y³ =
- 3(8x⁶ - 343y³) =
- 3[(2x²)³ - (7y)³] =
- 3(2x² - 7y)[(2x²)² + (2x²)(7y) + (7y)²] =
- 3(2x² - 7y)(4x⁴ + 14x²y + 49y²)
Used identity:
- a³ - b³ = (a - b)(a² + ab + b²)
Correct choice is C
Answer:
[tex]4x^4+14x^2y+49y^2[/tex]
Step-by-step explanation:
Given expression:
[tex]24x^6-1029y^3[/tex]
Factor out the common term 3:
[tex]\implies 3(8x^6-343y^3)[/tex]
Rewrite 8 as 2³ and 343 as 7³:
[tex]\implies 3(2^3x^6-7^3y^3)[/tex]
[tex]\textsf{Rewrite $x^6$ as $x^{2 \cdot 3}$}:[/tex]
[tex]\implies 3(2^3x^{2 \cdot 3}-7^3y^3)[/tex]
[tex]\textsf{Apply the exponent rule} \quad a^{bc}=(a^b)^c:[/tex]
[tex]\implies 3(2^3(x^2)^3-7^3y^3)[/tex]
[tex]\textsf{Apply the exponent rule} \quad a^cb^c=(ab)^c:[/tex]
[tex]\implies 3((2x^2)^3-(7y)^3)[/tex]
Apply the Difference of Cubes formula a³ - b³ = (a - b)(a² + ab + b²):
[tex]\implies 3(2x^2-7y)((2x^2)^2+(2x^2)(7y)+(7y)^2)[/tex]
[tex]\textsf{Apply the exponent rule} \quad (ab)^c=a^cb^c:[/tex]
[tex]\implies 3(2x^2-7y)(2^2x^4+2x^27y+7^2y^2)[/tex]
[tex]\implies 3(2x^2-7y)(4x^4+14x^2y+49y^2)[/tex]
Therefore, the only answer option that is a factor of the given expression is:
[tex]\boxed{4x^4+14x^2y+49y^2}[/tex]